The Virtuous Circle of Intellectual Capital and Corporate Environmentalism: Evidence from the Food Industry - Eugenio D’Angelo; Francesco Gangi; Lucia Michela Daniele; Nicola Varrone (European Scientific Journal, ESJ, 2021)
The purpose of this paper is to address the relationship between intellectual capital and corporate environmentalism, assuming that intellectual capital may be an important precondition to foster environmental commitment and that, on the other side, corporate environmentalism may positively determine the level of intellectual capital in a reciprocal and virtuous circle. To address this topic, we conducted two OLS regression analysis on a worldwide sample of 235 firms operating in the food industry, over an eight years’ time horizon (2010-2017), with 1,686 firm-year observations gathered from Asset-4ESG and Worldscope. Results confirm our hypotheses thus providing important theoretical and managerial implications.